PENGEMBANGAN KORELASI VISKOSITAS MINYAK BUMI BERDASARKAN KOMPOSISI - , Sudirman
Abstract : Oil viscosity is a function of composition, pressure, temperatures, and properties of heptane plus. In this research, it is developed the correlation of oil viscosity based on composition for fields in Indonesia. Correlation of Lohrenz et al. is used to calculate the viscosity of oil produced from some wells located in West Java and South Sumatera. The correlation gives errors of about 65.051 % compared to measured viscosity from laboratory. The research developed viscosity correlation based on correlation Lohrenz et al. The correlation gives errors of about 7.5% which have a better accuracy. To complete the result of research one set of nomograms is produced to get the viscosity value for different composition easily.